Oral Hygiene Practices and Awareness of Pregnant Women about the Effects of Periodontal Disease on Pregnancy Outcomes - Noora Mohammed Eissa Bushehab; Jayadevan Sreedharan; Sesha Reddy; Jovita D’souza; Hossam Abdelmagyd (International Journal of Dentistry)
Objectives. Adverse pregnancy outcomes, such as preterm low birth weight (PTLBW), is a severe public health issue that needs to be dealt with by educating the general female population, dental practitioners, and gynecologist. One of the major contributing factors is periodontal disease, which accounts for about 18.2% of all PTLBW cases worldwide, and prevention of the same could reduce the occurrence of PTLBW babies. This study aimed to assess the oral hygiene practices and awareness of pregnant women about the effect of periodontal disease on pregnancy outcomes. Methods. A descriptive cross-sectional study was conducted where 400 pregnant women after consent were requested to complete an anonymous, self-administered, structured questionnaire with twenty-one close-ended questions. Results. Only 5% of participants in this study reported that gum diseases during pregnancy lead to preterm labor or low birth weight babies. About 70.7% of pregnant women mentioned that they did not use any interdental cleaning aids, and 54.5% did not use mouthwashes. Conclusion. Tooth brushing practices among pregnant women were good; however, there was an overall lack in the use of adjunctive aids. The study highlighted a deficiency in the awareness of pregnant women regarding the association between periodontal disease and adverse pregnancy outcomes.